Pakistan, Politics and Political Business Cycles (The Pakistan Development Review, 2012)
This paper studies whether in Pakistan the dynamic behaviour of unemployment, inflation, budget deficit and real GDP growth is systematically affected by the timing of elections. We cover the period from 1973-2009. Our results can be summarised as follows: (1) Unemployment tends to be lower in pre-election periods and tends to increase immediately after elections, perhaps as a result of politically motivated employment schemes. (2) Inflation tends to be lower in pre-election periods, perhaps as a result of pre-electoral price regulation. (3) We find increase in the governmental budget deficit, financed by heavy government borrowings from the central bank and banking sector during election year. (4) Real GDP growth and real governmental investment growth declines during pre and post election terms possibly as a result of inefficient resource allocation. JEL Classification: D72, D78, H50, H61, E51 Keywords: Opportunistic Political Business Cycle, Fiscal Policy, Macroeconomics, Elections, Pakistan